Therapeutic exercise in fibromyalgia syndrome: a narrative review - Carlos Forner-Álvarez; Carlos Zanón-Chanzá; Ferran Cuenca-Martínez; Núria Sempere-Rubio (Exploration of Neuroprotective Therapy, 2024)
Fibromyalgia syndrome (FMS) is characterised by the presence of distributed pain in different areas of the body accompanied by the alteration of some functions such as the activity of the neurovegetative system, the sleep quality, or the presence of fatigue. The present narrative review aims to evaluate some key studies regarding the effects of different therapeutic exercise (TE) modalities on clinical variables of interest in patients with FMS, as well as to discuss some of the possible mechanisms of action of TE in improving pain intensity in patients with FMS. All aerobic, strengthening, and body-mind exercises were shown to bring about changes in the improvement of clinical variables of interest in patients with FMS. In addition, with regard to the improvement of pain intensity, there are different arguments that could explain the hypoalgesic effect of TE (structured in physical, neurophysiological, and psychosocial mechanisms). In conclusion, TE is a clinical tool with great potential for patients with FMS as it may produce hypoalgesia through physical, neurophysiological, and psychosocial mechanisms. All these TE modalities have demonstrated in isolation a remarkable effectiveness in the overall improvement of patients with FMS. However, more research is needed in this field especially on the long-term effects and on the combination of the different training modalities.